2017
DOI: 10.1371/journal.pone.0176923
|View full text |Cite
|
Sign up to set email alerts
|

Levels of infants’ urinary arsenic metabolites related to formula feeding and weaning with rice products exceeding the EU inorganic arsenic standard

Abstract: Early childhood inorganic arsenic (i-As) exposure is of particular concern since it may adversely impact on lifetime health outcomes. Infants’ urinary arsenic (As) metabolites were analysed in 79 infants by inductively coupled plasma—mass spectrometric detection (IC-ICP-MS) to evaluate i-As exposure pre- and post-weaning. Levels of i-As in rice-based weaning and infants’ foods were also determined to relate to urinary As levels. Higher As levels, especially of monomethylarsonic acid (MMA) and dimethylarsinic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 27 publications
3
29
0
1
Order By: Relevance
“…In fact, after the introduction of the European legislation in January 2016, a market survey in the United Kingdom identified that most baby rice products still exceed the maximum level set (Signes-Pastor et al, 2017). In such context, it should be emphasized that the nine samples from Mato Grosso presented total As content well below the maximum level of iAs set by the European legislation ( Figure 1).…”
Section: As Species In Brazilian Ricementioning
confidence: 99%
“…In fact, after the introduction of the European legislation in January 2016, a market survey in the United Kingdom identified that most baby rice products still exceed the maximum level set (Signes-Pastor et al, 2017). In such context, it should be emphasized that the nine samples from Mato Grosso presented total As content well below the maximum level of iAs set by the European legislation ( Figure 1).…”
Section: As Species In Brazilian Ricementioning
confidence: 99%
“…Rice-based foods consumed by infants, e.g. rice milk, syrup and formulae, can contain appreciable amounts of As (Meharg et al 2008a(Meharg et al , 2008bLjung et al 2011;Jackson et al 2012;Munera-Picazo et al 2014;Signes-Pastor et al 2017). Precooked milled rice is the primary carbohydrate source for weaning babies up to 1 year old and it has been reported that infants had high As concentrations in their hair from the consumption of rice in weaning diets (Ljung et al 2011;Hernández-Martínez and Navarro-Blasco 2013;Karagas et al 2016;Signes-Pastor et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ingestion of rice and rice products is reported to be a major dietary uptake of iAs for humans, especially among infants and young children who are at high risk of ingesting elevated levels of iAs due to high consumption of rice products per kg body weight (Munera-Picazo et al, 2014). In January 2016, The European Union (EU) legislated a maximum contaminant limit (MCL) of 0.250 mg/kg iAs for husked rice, 0.200 mg/kg iAs in rice and 0.100 mg/kg iAs in rice destined to produce baby food (Signes-Pastor et al, 2017; The Commission of the European Communities, 2015) ( Table S1) in order to protect infants, young children and the general population from ingesting elevated iAs levels through rice consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Not only has the EU set iAs MCL for rice, but other regulatory bodies have also set regional or country based MCL that range from 0.100 mg/kg (EU) to 0.300 mg/kg for iAs and up to 0.700 mg/kg for total arsenic (tAs) ( Table S1). A market survey on rice products destined for babies and infants, bought after the introduction of the MCL in the EU, found that almost 50% of the products did not comply with the legislation (Signes-Pastor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%